Using scrum for implementing IT governance with COBIT 5 - Amorim, A. C.; da Silva, M. M.; Pereira, R.; Gonçalves, M. (2018 IEEE 22nd International Enterprise Distributed Object Computing Conference (EDOC), 2018)
COBIT 5 is a widely-used framework for implementing sound governance of enterprise IT (GEIT). Despite the existence of official guidance, there are still several challenges that we can encounter. Currently, the ISACA's official implementation solution follows a sequentially ordered process corresponding to a traditional approach, however, organizations are increasingly embracing more agile ones for managing projects where the solution is not clear from the beginning. Using the Design Science Research Methodology, the authors analyse the current state of art and provide a Scrum based methodology for managing at team level a COBIT 5 programme. With a hybrid agile-traditional approach, the authors aim to eliminate some known challenges of COBIT 5, such as lack of support from top management and misaligned scopes and solutions. Additionally, in this paper, the authors present the results obtained from applying the designed methodology in a COBIT 5 programme in the Portuguese Finance Ministry, as well as inspect two series of interviews: 10 performed with experts from both Scrum and COBIT 5 areas to evaluate the solution, and 6 others with the team involved in the demonstration programme, to understand if the objectives where achieved. The article ends with lessons learned, limitations and future work.